2020
DOI: 10.3390/su12103964
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Weight Status on Cardiovascular Parameters Related to Physical Effort in Young Athletes

Abstract: Excess weight leads to an impaired cardiovascular response to physical exertion even at a young age. Sports training during youth promotes cardiovascular adaptations. The aim of the study is to verify the impact of weight status on cardiovascular parameters related to physical effort in young people who engage in competitive sports. A retrospective study was conducted on 8307 young athletes (5578 males and 2729 females) aged 6–18 years (mean age 13.9 ± 2.2 years). The data concerning graded exercise tests of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This study analyzed the performance of 1915 subjects aged 14–15 years to generate, for the first time, sex- and age-specific normative values for physical fitness for Florentine adolescents. These normative values are added to the existing standards for the Florentine youth population on other cardiovascular risk factors related to physical exertion [ 19 , 20 , 21 ], adiposity [ 22 ], body mass index [ 23 ], eating habits [ 24 ], and lifestyle [ 25 , 26 ]. Although these fitness percentiles are not directly linked to the health status of the youth population, they help to monitor the phases of health surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed the performance of 1915 subjects aged 14–15 years to generate, for the first time, sex- and age-specific normative values for physical fitness for Florentine adolescents. These normative values are added to the existing standards for the Florentine youth population on other cardiovascular risk factors related to physical exertion [ 19 , 20 , 21 ], adiposity [ 22 ], body mass index [ 23 ], eating habits [ 24 ], and lifestyle [ 25 , 26 ]. Although these fitness percentiles are not directly linked to the health status of the youth population, they help to monitor the phases of health surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the various weight classes are reported in other studies carried out on the same sample (Mascherini, Galanti, Massetti, Calà, & Modesti, 2019a;Mascherini, Petri, et al, 2019b). In particular, a previous study (Mascherini et al, 2020) showed that excess weight leads to an early chronotropic increase compared to the normal weight condition. Therefore, this information could be used in the clinical setting to evaluate the increase in heart rate compared to the normative values provided in the percentiles of this study.…”
Section: Anthropometric Parametersmentioning
confidence: 95%
“…However, this parameter shows limited variability in subjects with non-cardiovascular diseases and has little diagnostic value (Ahmad, Kavey, Kveselis, Gaum, & Smith, 2001). Obese young athletes have been shown to have a greater chronotropic response to exercise while achieving the same HR max compared to age-matched, normal-weight young athletes (Mascherini et al, 2020). Therefore, evaluating the chronotropic response during an incremental exercise might provide additional diagnostic information rather than using only HR max in the young population, both healthy and with cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%